Regulating cyberspace can it be done? - Mendoza, Amado M. Jr (Public Policy, 1999)
Touted for the most part as a revolutionary development with beneficial effects on the way people live, work and communicate, cyberspace has given rise to new and more complex types of legal issues. States are now confronted with the question of whether or not govern cyberspace. This presupposes the question of whether cyberspace is governable to begin with, and if so, how. This essay notes that although technological advances may seem to render it ungovernable, cyberspace, like real world markets, will require regulation if it is to remain relatively free to spur innovation and creativity.